MATERNAL ANTHROPOMETRY AND GROWTH OUTCOMES IN INFANTS AGED < 6 MONTHS: A CROSS-SECTIONAL STUDY: ANTROPOMETRI IBU DAN HASIL PERTUMBUHAN BAYI USIA < 6 BULAN: STUDI LINTAS SEKSI - Meutia Wardhanie Ganie; Dina Keumala Sari; Sarma Nursani Lumbanraja; Zaimah Z Tala; Winra Pratita (Faculty of Medicine Universitas Islam Sumatera Utara, 2026)
Maternal nutrition status during lactation plays an important role in supporting infant growth in early life through its influence on the quality and composition of breastmilk. However, evidence regarding tha association between maternal anthropometry and infant growth outcomes remains inconsistent across different populations. This study aimed to examine the association between maternal nutritional status and growth outcomes among infants aged <6 months. A cross-sectional analytic study was conducted among 56 mother-infant pairs in Medan,Indonesia, between September and November 2025. Maternal nutritional status was assessed using body mass index (BMI), while infant growth was evaluated using World Health Organization anthropometric indicators, including weight-for-age, length-for-age, weight-for-length, and BMI-for-age. Statistical analysis was performed using Spearman correlation. Significant positive correlation were observed between maternal nutritional status and infant weight-for-age (r=0.301; P=0.024), length-for-age (r=0.322; p= 0.0015), weight-for-lentgh (r=0.319; p=0.017), BMI-for-age (r=0.319; p=0.0017). Conclusion: Maternal nutritional status was significantly associated with infant growth indicators during the first six months of life. These findings highlight the importanace of maintaining optimal maternal nutrition during lactation to support healthy infant growth.